Method of tests on the fretting-wear of cylindrical surfaces with a gap - Милятинский, С.В.; Кузьменко, А.Г.; Криворотько, В.М.; Николаев, А.Н. (Problems of Tribology, 2014)
Method of tests on the fretting-wear of cylindrical surfaces with a gap